Association between waist-to-height ratio and insulin resistance in patients with polycystic ovary syndrome: a meta-analysis - Lan, Yuxiang; Zhong, Chaohao; Li, Dujin; Chen, Haobin; Dai, Xu (Frontiers in Endocrinology, 2025)
BackgroundInsulin resistance (IR) is regarded as a significant role in the pathophysiology of Polycystic Ovary Syndrome (PCOS), hence early identification of IR in PCOS patients is crucial for their treatment. Recent researches indicate that Waist-to-Height Ratio (WHtR) differs in patients with PCOS accompanied by IR compared to those with PCOS alone; however, a consensus has yet to be reached. This research presents a meta-analysis of current data to propose a straightforward new index for diagnosing PCOS with insulin resistance.ObjectiveThis study aims to assess the correlation between WHtR and insulin resistance in individuals with polycystic ovarian syndrome by meta-analysis and the synthesis of research information. This study will offer prognostic insights into the onset of insulin resistance in individuals with polycystic ovaries.MethodsThis systematic review has finalized registration (CRD42025638798) on the PROSPERO platform. We conducted a search of prominent databases, including PubMed, Embase, Web of Science, The Cochrane Library, and performed manual searches. Observational studies of relevance (cohort, case-control, or cross-sectional) published before January 13, 2025, were considered. The methodological quality of case-control studies and cohort studies was evaluated using the NOS tool. Simultaneously, AHRQ criteria were employed to evaluate cross-sectional research. The study outcomes were reported as mean ± sd. The aggregated data was analyzed using StataMP17.0.ResultsA meta-analysis encompassing nine studies with 3012 participants identified a significant correlation between an increased WHtR and the onset of insulin resistance in individuals with polycystic ovarian syndrome (SMD: 1.07, 95% CI: 0.81, 1.32, p = 0.000).ConclusionPatients with PCOS and insulin resistance will exhibit a greater WHtR compared to those with PCOS without insulin resistance. Thus, the incidence of insulin resistance in patients with polycystic ovary syndrome can be anticipated by monitoring the WHtR.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42025638798, identifier CRD42025638798.